Growth of Different Zinc Oxide Nanostructures for Hydrogen Gas Sensing - Thamir A.A. Hassan (Journal of Global Pharma Technology, 2019)
This work describes the synthesis of various Zinc Oxide (ZnO) nanostructures by a hydrothermal technique. The structures achieved included nanotubes, a lettuce leaf nanostructure and nanosticks, all starting from a ZnO nanostructure of 20 -30 nm and produced by thermal treatment in 6 M NaOH. The process did not use any catalyst or buffer layer and was carried out inside a purpose-built Teflon lined stainless steel autoclave, maintained at a temperature of 70 °C for 24, 48 and 72 hours. The reaction time had a significant influence on the morphology of the resulting products, whose crystallinity and structural properties were studied using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The FE-SEM images clearly show diffraction peaks associated with the Wurtzite hexagonal-shaped ZnO structure whilst AFM results show that the films produced have a high surface roughness, especially for the intermediate 48 h synthesis time. Nanostructures ultra-selective detection in gas phase lead to application of artificial sensing intelligence. In this paper, we show that fined the H2 gas concentrations on deliberately controlled sensor device toward specific prepare with ZnO nanostructure.  Keywords: ZnO, Nanostructure, Hydrothermal, IDE, Artificial intelligence.